A PRAGMATIC STUDY AND ITS TRANSLATION OF THE FACE CONCEPT IN DIANA PALMER'S CATTLEMANT'S PRIDE - Syaifulloh, Syaifulloh (PRASASTI: Journal of Linguistics, 2014)
This paper shows concept of face focused on positive and negative faces in theDiana Palmer‟s Cattlemant‟s Pride. The writer has tried to find forms ofexpressions containing positive and negative faces using qualitative contentanalysis method. From the findings and discussion, it is found that there are someforms of positive face under the categories of kidding and joking. Meanwhile in negative face, bold on record, deference and conventional indirectness. In terms of the translation, it can be said that the translation is good enough and tends to befree. Key Words: pragmatic, translation, face concept